Galectins: New agonists of platelet activation - Schattner, Mirta Ana (2013)
Platelet activation at sites of vascular injury leads to the formation of a hemostatic plug and is crucial for hemostasis. However, uncontrolled platelet activation may lead to the formation of occlusive thrombi. Several soluble or matricellular proteins can activate platelets. In this article we review recent advances on the role of galectins in platelet physiology. Either in soluble or immobilized form, these endogenous glycan-binding proteins trigger platelet activation through modulation of discrete signaling pathways. We discuss the role of platelet-galectin interactions not only in hemostasis, but also in chronic inflammation, atherosclerosis and cancer.